The Evolution of Mentorship Capacity Development in Low- and Middle-Income Countries: Case Studies from Peru, Kenya, India, and Mozambique - Emília Virgínia Noormahomed; Pamela Williams; Andrés G. Lescano; Tony Raj; Elizabeth A. Bukusi; Robert T. Schooley; Craig R. Cohen (2018)
Following the Fogarty International Center-supported "Mentoring the Mentors" workshops in South America, Africa, and Asia, approaches and guidelines for mentorship at institutions within these low- and middle-income country (LMIC) contexts, appropriate for the respective regional resources and culture, were implemented. Through the presentation of case studies from these three geographic regions, this article illustrates the institutional mentorship infrastructure before the workshop and the identified gaps used to implement strategies to build mentorship capacity at the Universidad Peruana Cayetano Heredia (Peru), Kenya Medical Research Institute (Kenya), Saint John's Research Institute (India), and Eduardo Mondlane University (Mozambique). These case studies illustrate three findings: first, that mentorship programs in LMICs have made uneven progress, and institutions with existing programs have exhibited greater advancement to their mentoring capacity than institutions without formal programs before the workshops. Second, mentoring needs assessments help garner the support of institutional leadership and create local ownership. Third, developing a culture of mentorship that includes group mentoring activities at LMIC institutions can help overcome the shortage of trained mentors. Regardless of the stage of mentoring programs, LMIC institutions can work toward developing sustainable, culturally effective mentorship models that further the partnership of early career scientists and global health.